AN ANALYSIS ON Pb(IV) ION EFFECTS TOWARDS DETERMINING Fe(II) WITH 1,10-PHENANTROLINE ON pH 4,5 USING UV-VIS SPECTROPHOTOMETER - Djarot Sugiarso; Rizkika Widianti; Kamila Zahranisa; Suprapto Suprapto; Herdayanto S Putro; Ratna Ediati (LPPM, Institut Teknologi Sepuluh Nopember, 2023)
An analysis on the effects of Pb(IV) towards determining Fe(II) with 1,10-phenantroline complex on pH 4,5 using UV-VIS spectrophotometer have been conducted. Fe(II) phenatroline complex have maximum wavelength of 508 nm. Pb(IV) ion as an ion disturber have a maxium wavelength of 315 nm. The relation coefficient obtained from the calibrated curve is 0,997 with the linear equation y = 0,118x + 0,020. By obtaining Pb(IV) ions, they could increase the iron concentration when it reached 0,2 ppm with recovery percentage of 123,160 and disturbed the iron concentration when it reached a concentration of 6 ppm with recovery percentage of 71,108